2009
DOI: 10.3201/eid1501.080299
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Hygiene Measures and Norovirus Transmission during an Outbreak

Abstract: Control of norovirus outbreaks relies on enhanced hygiene measures, such as handwashing, surface cleaning, using disposable paper towels, and using separate toilets for sick and well persons. However, little is known about their effectiveness in limiting further spread of norovirus infections. We analyzed norovirus outbreaks in 7 camps at an international scouting jamboree in the Netherlands during 2004. Implementation of hygiene measures coincided with an 84.8% (95% predictive interval 81.2%-86.6%) reduction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(36 citation statements)
references
References 31 publications
3
32
0
1
Order By: Relevance
“…Vulnerable people such as the elderly, immunocompromised or the very young can require additional care (Harris et al 2008). Outbreaks of NoV frequently occur in high-density settings such as care homes, hospitals, and cruise ships; however, outbreaks in restaurants, hotels, holiday camps and through consumption of contaminated drinking water are also commonplace (Heijne et al 2009; Werber et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Vulnerable people such as the elderly, immunocompromised or the very young can require additional care (Harris et al 2008). Outbreaks of NoV frequently occur in high-density settings such as care homes, hospitals, and cruise ships; however, outbreaks in restaurants, hotels, holiday camps and through consumption of contaminated drinking water are also commonplace (Heijne et al 2009; Werber et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…For example, Vega and colleagues, reviewing norovirus trends in the United States from 2009 to 2013, demonstrated that GII.4 was more likely to be associated with person-to-person transmission, especially in long-term-care facilities (LTCFs) and hospital settings, whereas GI.7 and GII.12 were more frequently associated with foodborne disease (103). The environmental durability of norovirus leads to persistence of the pathogen in clinical settings and other closed-space environments, thus complicating complete disinfection and allowing for recurrent outbreaks (104,105).…”
Section: Epidemiologymentioning
confidence: 99%
“…This method, originally described by Wallinga and Teunis, requires only onset dates of all cases in the outbreak and knowledge of the probability distribution of the serial interval for the specific infectious disease [17]. We used a serial interval for norovirus derived from several large norovirus outbreaks in child daycare centers in Sweden with a gamma probability distribution, mean of 3.6 days, and standard deviation of 2.0 days [19]. We performed sensitivity analyses with mean serial intervals varying between 1.5 and 4.0 days in half day increments (S2 RMarkdown File).…”
Section: Estimation Of Reproduction Numbersmentioning
confidence: 99%
“…We performed sensitivity analyses with mean serial intervals varying between 1.5 and 4.0 days in half day increments (S2 RMarkdown File). Details of the estimation procedure are available elsewhere [17,19,20]. Briefly, this method uses the difference in symptom onsets dates between cases and the probability distribution of the serial interval to calculate the relative likelihood that cases with earlier symptom onset dates infected cases with later symptom onset dates.…”
Section: Estimation Of Reproduction Numbersmentioning
confidence: 99%